Betaine‐homocysteine S‐methyltransferase deficiency causes increased susceptibility to noise‐induced hearing loss associated with plasma hyperhomocysteinemia. Issue 5 (12th February 2019) - Partearroyo, Teresa; Murillo‐Cuesta, Silvia; Vallecillo, Néstor; Bermúdez‐Muñoz, Jose M.; Rodríguez‐de LaRosa, Lourdes; Mandruzzato, Giacomo; Celaya, Adelaida M.; Zeisel, Steven H.; Pajares, María A.; Varela‐Moreiras, Gregorio; Varela‐Nieto, Isabel
ABSTRACT: Betaine‐homocysteine S‐methyltransferases (BHMTs) are methionine cycle enzymes that remethylate homocysteine; hence, their malfunction leads to hyperhomocysteinemia. Epidemiologic and experimental studies have revealed a correlation between hyperhomocysteinemia and hearing loss. Here, we have studied the expression of methionine cycle genes in the mouse cochlea and the impact of knocking out the Bhmt gene in the auditory receptor. We evaluated age‐related changes in mouse hearing by recording auditory brainstem responses before and following exposure to noise. Also, we measured cochlear cytoarchitecture, gene expression by RNA‐arrays and quantitative RT‐PCR, and metabolite levels in liver and plasma by HPLC. Our results indicate that there is an age‐dependent strain‐specific expression of methionine cycle genes in the mouse cochlea and a further regulation during the response to noise damage. Loss of Bhmt did not cause an evident impact in the hearing acuity of young mice, but it produced higher threshold shifts and poorer recovery following noise challenge. Hearing loss was associated with increased cochlear injury, outer hair cell loss, altered expression of cochlear methionine cycle genes, and hyperhomocysteinemia. Our results suggest that BHMT plays a central role in the homeostasis of cochlear methionine metabolism and that Bhmt2 up‐regulation could carry out a compensatory role in cochlear protection against noise injury in the absence of BHMT.—Partearroyo, T., Murillo‐Cuesta, S., Vallecillo, N., Bermúdez‐Muñoz, J. M., Rodríguez‐de la Rosa, L., Mandruzzato, G., Celaya, A. M., Zeisel, S. H., Pajares, M. A., Varela‐Moreiras, G., Varela‐Nieto, I. Betaine‐homocysteine S ‐methyltransferase deficiency causes increased susceptibility to noise‐induced hearing loss associated with plasma hyperhomocysteinemia. FASEB J. 33, 5942–5956 (2019). www.fasebj.org